Baker, Herbert (Sir) and Masey. New Modderfontein Staff Houses Type B. Jun 1910. Plans sections & elevations. Watercolour paints on paper. - Baker & Masey, Herbert (Sir) (My University, 2012)
Baker, Herbert (Sir) and Masey. New Modderfontein Staff Houses Type B. Jun 1910. Plans sections & elevations. Watercolour paints on paper.
Ink & watercolour paints on paper. 645X460
Keywords: Baker, Herbert (Sir) and Masey. New Modderfontein Staff Houses Type B. Jun 1910. Plans sections & elevations. Watercolour paints on paper.